Black well-being : health and selfhood in antebellum black literature - Stone, Andrea, 1971- (University Press of Florida, 2016)
By analyzing slave narratives, emigration polemics, and black-authored fiction pieces, Stone reveals many reflections of injury, illness, disease, and disability, but she also highlights the equally numerous emphases on well-being by black authors.